Determinasi Minat Beli Konsumen Terhadap Skincare Skintific di TikTok Shop Palembang - Gracia Natasya Valentine; Kardinal - (Universitas Multi Data Palembang, 2026)
This study aims to analyze the influence of Brand Ambassador, Product Quality, E-WOM, and Brand Image on Buying Interest in Skintific Skincare Products at E-Commerce TikTok Shop in Palembang City. The study used a quantitative approach with a survey method through the distribution of questionnaires to 221 respondents who were selected using the Probability Sampling technique with the cluster random sampling method in 18 sub-districts. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results of the study show that partially and simultaneously, all independent variables have a positive and significant effect on buying interest. In conclusion, increasing consumer buying interest can be achieved through the selection of credible Brand Ambassadors. Consistent Product Quality, Positive E-WOM, and Good Brand Image.